Enteroparasitoses em escolares atendidos na rede pública de ensino do município de Mirassol, Noroeste Paulista - Belloto, Marcus Vinicius Tereza (2010)
This study aimed to reevaluate the prevalence of intestinal parasites in students from public schools and to investigate possible epidemiological association of socio-economic development. From September 2009 until March 2010, we analyzed a stool sample of students enrolled in the School Hall Darci Amancio, the city of Mirasol, in São Paulo. We collected fecal samples from 310 children whose parents or guardians agreed to participate. About 30.32% of children had at least one intestinal parasite. The protozoan Giardia lamblia was the most frequent, followed by Entamoeba histolyttica. Helminths detected were Ascaris lumbricoides, Strongiloides stercoralis and Taenia sp. Showed a reduction in the rate of parasitism in this population after ten years of research, however, there is a greater diversity of parasites infecting these children. The use of tap water was incriminated by favoring parasitism. Moreover, the use of mineral water proved to be protecting against it. The continuous monitoring of intestinal parasites in different regions of the country aimed at clarifying the importance of each of these agents in the etiology of diarrhea in children. Although we have not associated the presence of intestinal parasites in gastrointestinal disorders, the presence of these agents can boost the new cases, as these children can act as carriers and therefore a source of contamination.